Effects of Tiaopi Xiezhuo decoction on constipation and gut dysbiosis in patients with peritoneal dialysis. (31st December 2023) - Peng, Yu; Zeng, Yuting; Zheng, Tingting; Xie, Xiaoning; Wu, Jianfeng; Fu, Lizhe; Lu, Fuhua; Zhang, La; Chen, Yang; Liu, Xusheng; Wang, Lei
Abstract: Context: A Chinese herbal formula, Tiaopi Xiezhuo decoction (TXD), is developed from a classical Chinese prescription Sanhuang Xiexin decoction. Objective: To investigate the regulatory effect of TXD on gut dysbiosis, as a treatment of constipation in patients with peritoneal dialysis (PD). Materials and methods: The chemical content of TXD was assessed by high-performance liquid chromatography. A total of 29 PD patients were enrolled and treated with TXD orally (3 g crude drug/each/twice/day) for 3 months. Blood and faecal samples were collected at the beginning and end, to determine the changes in biochemical characteristics and gut microbial composition. The stool conditions were asked to be scored. Additional 30 healthy individuals were recruited as a control for the analysis of gut microbiota. Results: Although having no significant effects on serum biochemical characteristics, 3-month TXD intervention improved constipation in PD patients: decreased 80% abdominal distention ( p  < 0.01), increased 2.6-fold sloppy stools ( p  < 0.05) and eliminated hard stool completely ( p  < 0.01). The analysis of gut microbiota showed that, compared to the healthy group, the microbial richness was reduced in PD patients. After a 3-month TXD treatment, this reduced richness was raised, and Paraprevotella clara, Lachnospiraceae bacterium 2-146FA, Phascolarctobaterium succinatutens, Lachnospiraceae bacterium 2-1-58FAA, Fusobacterium mortiferum, and Prevotella copri were accumulated in the intestinal flora. Furthermore, the bacterial species enriched by TXD correlated with the improvement of constipation. Discussion and conclusions: TXD treatment may improve constipation by modulating gut dysbiosis in PD patients. These findings provide data to support the further application of TXD in the adjuvant treatment of PD.